2021
DOI: 10.1007/s11307-021-01683-0
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Validated Intracellular ROS Generation with 18F-dihydroethidine-Based PET

Abstract: Purpose To determine the sensitivity of the 18F-radiolabelled dihydroethidine analogue ([18F]DHE) to ROS in a validated ex vivo model of tissue oxidative stress. Procedures The sensitivity of [18F]DHE to various ROS-generating systems was first established in vitro. Then, isolated rat hearts were perfused under constant flow, with contractile function monitored by intraventricular balloon. Cardiac uptake of infused [18F]DHE (50–150 kBq.min−1) was monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…DHE is one of the most commonly used superoxide anion fluorescent probes, which can effectively detect ROS levels [56]. After staining with DHE, the mycelia of the ∆Aoprdx2 mutant accumulated more ROS compared with the WT strain (Figure 5A).…”
Section: Aoprdx2 Regulates Ros Accumulation and Endocytosismentioning
confidence: 99%
“…DHE is one of the most commonly used superoxide anion fluorescent probes, which can effectively detect ROS levels [56]. After staining with DHE, the mycelia of the ∆Aoprdx2 mutant accumulated more ROS compared with the WT strain (Figure 5A).…”
Section: Aoprdx2 Regulates Ros Accumulation and Endocytosismentioning
confidence: 99%
“…Ex vivo studies showed that the uptake of [ 18 F] 6 was significantly greater in menadione-treated hearts than in normal heart. Moreover, the higher uptake of [ 18 F] 6 was also associated with concomitant cardiac contractile dysfunction …”
Section: Radiotracers Based On Fluorescent Moleculesmentioning
confidence: 99%
“…Moreover, the higher uptake of [ 18 F]6 was also associated with concomitant cardiac contractile dysfunction. 29 1.2. Radionuclide Labeled Hydrocyanine Derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%